On the Strong Law of Large Numbers for Multivariate Martingales with Continuous Time - Koval, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We prove the strong law of large numbers for vector martingales with arbitrary operator normalizations. From the theorem proved, we deduce several known results on the strong law of large numbers for martingales with continuous time.